2003
DOI: 10.1002/jat.935
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and biochemical changes in lung tissues of rats following administration of fluoride over several generations

Abstract: The possible effects of multigenerational administration of sodium fluoride (NaF) via drinking water on lung tissue morphology and biochemistry and body and lung weight were investigated in second-generation adult male rats. For this purpose we selected 45 Albino adult Wistar rats in nine cages, each of which consisted of four females and one male. Twenty-eight pregnant rats were selected for the experiment, divided into four groups of seven rats given 1 (control group), 10, 50 and 100 mg l(-1) NaF in drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 33 publications
(22 reference statements)
2
25
0
1
Order By: Relevance
“…In addition, F, which is biologically active even at the lowest concentrations, can readily penetrate into cell membranes by simple diffusion and cause adverse effects on cell metabolism and function. Exposure to NaF (50, 100 mg/kg) through drinking water during gestation has resulted in histopathological changes, such as alveolar cell hyperplasia and necrosis in the lungs of rats over several generations [12]. In addition, administration of NaF (40 mg/kg) in rats during pregnancy and lactation was observed to result in hypoproteinemia and hypoglycemia in mothers and offspring [13].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, F, which is biologically active even at the lowest concentrations, can readily penetrate into cell membranes by simple diffusion and cause adverse effects on cell metabolism and function. Exposure to NaF (50, 100 mg/kg) through drinking water during gestation has resulted in histopathological changes, such as alveolar cell hyperplasia and necrosis in the lungs of rats over several generations [12]. In addition, administration of NaF (40 mg/kg) in rats during pregnancy and lactation was observed to result in hypoproteinemia and hypoglycemia in mothers and offspring [13].…”
Section: Introductionmentioning
confidence: 97%
“…The study of more than one generation allows detection not only of any effects on adult reproduction but also of effects on subsequent generations due to exposure in utero and early postnatally. The latest evaluation of sodium fluoride administration through multiple generations has been made previously in general aspects by Collins et al [18,19], in the myocardium, lung, kidney, and testis by Cicek et al [20], Aydin et al [21], Karaoz et al [22], and Meral et al [23] respectively, but brain tissue has not been studied specifically in multigeneration animals. Due to the lack of information on multigeneration studies concerning fluoride-induced changes on the thyroid hormone status, the histopathology of discrete brain regions, and the resultant alterations in acetylcholine esterase levels and the learning and memory abilities, the present study was undertaken.…”
mentioning
confidence: 99%
“…Meral et al [26] reported a significant increase in TBARS level in the testes of both first-and second-generation rats when compared to control, and the TBARS levels of second-generation rats were significantly higher than those of first-generation rats. Aydin et al [27] reported a significant increase in TBARS levels in lung tissues in groups treated with 50 and 100 mg/L fluoride over several generations. Similarly, Karaoz et al [28] showed that chronic fluorosis can lead to enhanced lipid peroxidation and kidney tissue alterations in first-and secondgeneration rats.…”
Section: Discussionmentioning
confidence: 99%